Analisis pembelajaran keterampilan menyimak teks eksplanasi pada peserta didik kelas v sekolah dasar - Indriana Dewi; Riyadi Riyadi; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2022)
This study aims to determine learning activities of listening to explanation text in grade V students of SD Negeri Wonosri and obstacles in learning activities of listening to explanation text in grade V students of SD Negeri Wonosri. This research was conducted using qualitative methods. Data were collected through interviews, observation, and documentation. Research subject was collected using purposive sampling techniques combine with time sampling techniques. The data validity is done through triangulation techniques, namely the triangulation of sources and times. The data analysis used is interactive analysis model. The research showed that learning activities of listening to explanation text in grade V SD Negeri Wonosri applied the lecture method. Students are still less skilled in listening to explanatory texts seen from the attention, sincerity, liveliness, and enthusiasm. The teacher has provided a variety of explanation texts and have mastered of several pedagogic skills.Obstacles in learning activities of listening to explanation text in grade V SD Negeri Wonosri including the teacher-centered learning so that boredom is seen in students. The lack of media or learning variations makes students bored and less enthusiastic. Next, the class condition is not comfortable and the ability to listen to students is still low.